Determinants of Tea Preference: A Descriptive Analysis - Jaiswal, Nisha; Aryal, Narayan Prasad (Nepalese Journal of Business and Management Studies, 2022)
The study was designed to investigate the determinants of tea preferences among tea lovers in Sorakhutte, Kathmandu. A conceptual system was structured by considering theory of satisfaction and consumers’ preference talks about how the consumer is willing to consume tea. Price, habit, peers’ influence and taste are considered as predictors and consumers’ preference is taken as the reliant variable. Organized survey was performed among tea lovers in Sorakhutte using convenience sampling method and 103 usable questionnaires were utilized to analyse the collected data. The study employed descriptive research design and various tools such as frequency, percentage, bar-diagram, mean, median, and standard deviation were used for data analysis. The findings revealed that all the predictors i.e., price, habit, peers’ influence and taste have effect on tea preferences as the mean values were above 3.0. Among all of them, the study concluded that taste is the most important predictor for tea preferences. Further, the study also concluded the majority of tea lovers prefer loose tea in compare to branded and green tea and rated the friends as the most preferred companion to drink tea.